1989
DOI: 10.1007/bf00687247
|View full text |Cite
|
Sign up to set email alerts
|

Decreased activity of cytochromec oxidase in the macular mottled mouse: an immuno-electron microscopic study

Abstract: The macular mottled mouse is a murine model of the kinky hair syndrome, characterized by a deficiency in copper transport. Cytochrome c oxidase (CCO), a respiratory enzyme, is located in the inner mitochondrial membrane and consists of seven subunits, along with copper and iron. Biochemical and histochemical findings indicated that CCO activity was decreased in the cerebellum of the macular mottled mice but not in that of the controls. Immunocytochemical analysis, using anti-CCO and anti-complex III rabbit ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recent biochemical findings in cerebella of CuD rats on CCO function and expression confirm that cerebellum is a sensitive target of dietary copper limitation [19,20]. Both macular and brindled mice mutants also show reduced CCO activity [21,22]. These results provide a biochemical rationale for the cerebellar dysfunction and ataxia seen in dietary copper deficiency and Menkes disease.…”
Section: Introductionmentioning
confidence: 60%
“…Recent biochemical findings in cerebella of CuD rats on CCO function and expression confirm that cerebellum is a sensitive target of dietary copper limitation [19,20]. Both macular and brindled mice mutants also show reduced CCO activity [21,22]. These results provide a biochemical rationale for the cerebellar dysfunction and ataxia seen in dietary copper deficiency and Menkes disease.…”
Section: Introductionmentioning
confidence: 60%
“…We have found that there is no appreciable difference in the levels of nearly 80 mitochondrial proteins including complex IV subunits in the Menkes mitochondrial proteome (unpublished data). The most consistent finding concerning complex IV is a reduction in the cytochrome oxidase C enzymatic activity (Hunt, 1977; Kodama et al, 1989; Kunz et al, 1999; Kuznetsov et al, 1996; Maehara et al, 1983; Meguro et al, 1991; Seki et al, 1989). Despite this decreased activity, the metabolism of high-energy phosphate compounds, such as ATP, does not seem to be affected in mouse cells lacking Atp7a (Kunz et al, 1999; Kuznetsov et al, 1996).…”
Section: The Oligoenzymatic Pathogenic Hypothesis Of Menkes Diseasementioning
confidence: 80%
“…Cytochrome oxidase C is a 13-subunit copper-dependent complex necessary for oxidative phosphorylation (Saraste, 1999). Decreased content of cytochrome oxidase C subunits have been frequently reported in human cells in culture and mouse tissues affected by Menkes (Hunt, 1977; Kodama et al, 1989; Kumode et al, 1994; Kunz et al, 1999; Kuznetsov et al, 1996; Maehara et al, 1983; Meguro et al, 1991; Rezek and Moore, 1986; Rossi et al, 2001; Seki et al, 1989; Sparaco et al, 1993; Yoshimura et al, 1990). This is in contrast with our quantitative mass spectrometry studies performed in cultured Menkes fibroblasts.…”
Section: The Oligoenzymatic Pathogenic Hypothesis Of Menkes Diseasementioning
confidence: 99%